Generation of an integration-free induced pluripotent stem cell line, MURAi006-A, from a hemoglobin E/β-thalassemia patient harboring the βE/β0 (Codon 17, A > T) compound heterozygous mutation - Pawarit Innachai; Gunn Pornratananont; Chonthicha Satirapod; Usanarat Anurathapan; Duantida Songdej; Amornrat Tangprasittipap; Suradej Hongeng (Stem Cell Research)
The HBB gene encodes the β-globin protein, one of the two main components of adult hemoglobin A (HbA) responsible for oxygen transport. β-thalassemia is a genetic disorder caused by mutations affecting β-globin chain synthesis, leading to reduced or absent β-globin production, impaired erythropoiesis, and generally results in anemia. In this study, the human-induced pluripotent stem cell line (hiPSC) MURAi006-A was generated from male fetal skin fibroblasts carrying both a β⁰-thalassemia mutation at codon 17 (A > T) and a codon 26 (G > A) HbE mutation using non-integrative reprogramming episomes.